Examining the Criminal Aspects of the Indonesian Plant Varieties Regime and Farmer Protection for Food Sovereignty - Suastuti, Eny; Haq, Hayyan Ul; Hasanah, Uswatun; Martini, Dwi; Lestari, Sartika Nanda (Journal of Indonesian Legal Studies, 2023)
This research investigates the Plant Varieties Regime's role in safeguarding farmers’ rights in plant development and cultivation in Indonesia. Specifically, it scrutinizes criminal provisions concerning farmers accused of producing seeds without the right holder's consent, as evident in multiple court decisions. These verdicts have ignited legal debates that conflict with the principles of food sovereignty. Given that nearly 90% of corn plants are cultivated through traditional farmer knowledge, the increasing dependence on the seed industry disrupts agricultural practices passed down through generations. The Plant Variety Protection Act (PVP Act) inadvertently encourages seed industry monopolization. This paper advocates a coherent approach in compliance with Article 27(2) of the 1945 Constitution to address these legal issues and establish a just legal framework. The primary legal discourse centers on equitable protection, necessitating a re-evaluation of the PVP Law, which is perceived as restricting plant development opportunities and discriminating against farmers. Farmers, as stewards of seed development and livelihood, should not face criminal charges encroaching upon their rights. Employing a normative methodology involving statutory, conceptual, and case analyses, this study examines the criminal aspects and legal protection of farmers' rights in corn seed cultivation. Ultimately, the paper recommends revising the PVP Law, emphasizing the importance of coherent legal thinking when shaping criminal policies. On a practical level, it calls for collaborative efforts among stakeholders to bolster agricultural sovereignty, particularly in the corn sector, by prioritizing farmers' rights. In summary, this research aims to provide recommendations for enhancing farmers' protection against the criminal provisions outlined in the PVP Act, which holds a pivotal role in shielding farmers engaged in corn seed cultivation.